Audience perception of media messages on environmental cleanliness in Port Harcourt, Rivers State, Nigeria - Somtochukwu Victor Okeke; Ambrose O. Igboke; Uzoamaka Chioma Ogor; Peace Nwamaka Ojonta; Robert C. E. Ezeanwu; Emeka S. S. Orekyeh; Goodness Oluebube Nwaneji; Charles Chukwudi Eze; Obioma R. Ozioko (Environment and Social Psychology, 2026)
This study investigates audience perception of media messages promoting environmental cleanliness in Port Harcourt, Nigeria, a city facing critical challenges of black soot pollution and ineffective solid waste management. It aims to assess awareness, exposure, frequency, and perception of such media messages to understand their impact on public engagement and behaviour. Employing a quantitative survey design, data were collected from 385 adult residents across selected Port Harcourt areas using a structured questionnaire. Sampling involved multi-stage cluster and purposive techniques to ensure demographic and geographic representativeness. The analysis focused on percentages and frequencies to capture audience responses regarding environmental media messaging. Results indicate moderate to high awareness of environmental messages, particularly regarding pollution control and waste disposal, with television and radio as dominant channels. Exposure was sustained, but frequency and consistency of messaging exhibited ambivalence. Audience perceptions were largely positive, highlighting message clarity, local relevance, practicality, and motivational impact; visual demonstrations and expert opinions were most compelling. Behavioural responses varied, with information sharing and community cleanup participation prevalent, but lower rates of recycling and proper waste disposal point to infrastructural and socio-economic barriers. The findings support agenda-setting theory by demonstrating media’s role in elevating environmental issues on the public agenda yet reveal gaps in media coverage and engagement depth. Effective environmental communication requires integrated media strategies and supportive policy frameworks, emphasizing clear, credible, and actionable messaging to foster sustainable urban environmental practices.